Ground and surface water hydrology - Mays, Larry W. (Wiley, 2012)
"Larry Mays' Hydrology is a comprehensive text stressing fundamentals of hydrologic process for both surface water hydrology and groundwater hydrology. The text makes use of internet resources, such as free modeling tools, to help solve more complicated and real-world problems more quickly, and motivate interest in the topics.The book focuses on Water Resources Engineering as a subset of Hydrology and Water Resources Engineering covering sources of water that are useful to humans. Hydrology includes both water resources engineering, and more in-depth coverage of the hydrologic cycle (the continuous circulation of water in the atmosphere, land, surface water, and groundwater). The hydrologic effects of climate change is covered, as well as newer topics in hydrology including use of GIS, remote sensing, NEXRAD and other topics. Emphasis is given to the hydrologic processes and practice in the different climates: humid climate, cold climate, temperate climate, and arid and semi-arid climate"--